1999
DOI: 10.1002/(sici)1096-9071(199904)57:4<390::aid-jmv11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral diarrhea in children in Beijing, China

Abstract: A study was undertaken from November 1994 to August 1996 to determine the role of viruses in children (< or =5 years of age) hospitalized at Beijing Children Hospital, Beijing China, for acute diarrhea. Stool samples from diarrheal patients were investigated by ELISA, electron microscopy, and RT-PCR for the presence of rotavirus, calicivirus, astrovirus, and adenovirus. Group A rotavirus was detected in 55.9% of all diarrheal patients and comprised 82.5% of all viruses detected. Group A rotavirus samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
2
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 35 publications
6
35
2
1
Order By: Relevance
“…This might partly be explained by the fact that older children acquired protective immunity during previous exposures to rotavirus and are therefore more resistant to infection with this agent (13,20). In addition to the age distribution of rotavirus infection, many studies have indicated a higher ratio of infected males to infected females (8,24,26,28,30). The ratio in our study was 1.9.…”
Section: Rotavirus Infectionmentioning
confidence: 44%
“…This might partly be explained by the fact that older children acquired protective immunity during previous exposures to rotavirus and are therefore more resistant to infection with this agent (13,20). In addition to the age distribution of rotavirus infection, many studies have indicated a higher ratio of infected males to infected females (8,24,26,28,30). The ratio in our study was 1.9.…”
Section: Rotavirus Infectionmentioning
confidence: 44%
“…In our study, P [6] strains were identified in combination with G9 (35.5%), G4 (25.8%), G1 (22.6%), and G3 (16.1%) serotypes and accounted for 10.7% of all P-typed specimens. In the present study, eight P [9] strains were isolated from children in six regions, and all were serotype G1, in contrast to a single P [9]G3 isolate from Wuhan, Hubei Province, detected in 1995 (25). In total, only 37 (11.3%) specimens were nontypeable by use of genotype-specific primers to five human rotavirus genotypes, suggesting that other P genotypes might be present or that variants of known genotypes could not be amplified with these primers.…”
mentioning
confidence: 66%
“…The incidence of norovirus infections in young children has been investigated in different regions worldwide. Several reports indicate that 7 to 9% of acute gastroenteritis cases among young children are caused by norovirus (12,16,20,22). However, other studies have reported higher incidence rates, ranging from 15.7 to 20% (6,11,18).…”
mentioning
confidence: 99%